2003
DOI: 10.1177/0011128703256526
|View full text |Cite
|
Sign up to set email alerts
|

Opening the Manager's Door: State Probation Officer Stress and Perceptions of Participation in Workplace Decision Making

Abstract: Stress can be costly not only to individuals but also to organizations. Participatory management has been recommended as a means for reducing probation officer stress. This article via self-report surveys of probation personnel in a southern state considers the relationship of a number of demographic variables with employee perceptions of participation in workplace decision making, job satisfaction, and organizational and physical stress levels. Construction of a structural model revealed that employee percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 37 publications
4
46
0
Order By: Relevance
“…The dependent variable for this study is the Selye Stress Scale, which has found utility for measuring physical stress levels among those working in criminal justice related occupations (Slate et al 2003;Slate and Vogel 1997;Cheek 1984;Cheek and Miller 1982a). This scale is comprised of a 54 item questionnaire which asks the respondent to rank his/her physical symptoms and associated severity on a 6 point Likert scale (Cheek and Miller 1982b).…”
Section: Dependent Variablementioning
confidence: 99%
See 2 more Smart Citations
“…The dependent variable for this study is the Selye Stress Scale, which has found utility for measuring physical stress levels among those working in criminal justice related occupations (Slate et al 2003;Slate and Vogel 1997;Cheek 1984;Cheek and Miller 1982a). This scale is comprised of a 54 item questionnaire which asks the respondent to rank his/her physical symptoms and associated severity on a 6 point Likert scale (Cheek and Miller 1982b).…”
Section: Dependent Variablementioning
confidence: 99%
“…Drawing from scales created by Spielberger et al (1981) [note, these scales have been used previously to examine police stress, see Storch and Panzarella 1996;Tang and Hammontree 1992;Thomas-Riddle 1999;Violanti and Aron 1994; a modified version of these scales has been used in probation officer stress research, see Slate et al (2003); Wells et al (2006);Whisler 1994], four stress scales were utilized as independent variables. These respective subscales assessed stress that was job or task related, external to the organization, internal to the agency, and personal in nature.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to the various stress categories (mentioned above), organizational stress refers to the stress coming from the organization for which the officer works, where factors like having a lack of input into organizational affairs can cause stress for officers (see also Slate, Wells, & Johnson, 2003), as can unsatisfactory pay and a lack of promotion potential (see Simmons, Cochran, & Blount, 1997;Whisler, 1994;Whitehead, 1986), and role conflict (see also Brown, 1987;Whitehead, 1985Whitehead, , 1986. In addition to organizational pressures, probation officers are subject to pressures coming from other government officials and the media, as social, political, and economic factors weigh on the work of the individual probation officer (Davidson, 1976;Mawby & Worrall, 2011;Worrall & Mawby, 2013).…”
Section: Literature On Community Corrections Health and Wellnessmentioning
confidence: 99%
“…Additionally, Slate et al (2003) contend participatory management schemes that allow officers more input into organizational decisions reduces stress. Finally, Pitts (2007) found less educated officers experienced higher levels of stress and contends officers can reduce stress levels by forming social support networks within their community corrections organizations.…”
Section: Organizational Efforts To Reduce Occupational Stress In Commmentioning
confidence: 99%